Incretins Enhance PGF2α-Induced Synthesis of IL-6 and Osteoprotegerin in Osteoblasts - Hioki, Tomoyuki; Kuroyanagi, Gen; Fujita, Kazuhiko; Sakai, Go; Kawabata, Tetsu; Kim, Woo; Tachi, Junko; Matsushima-Nishiwaki, Rie; Iida, Hiroki; Kozawa, Osamu; Tokuda, Haruhiko (Hormone and Metabolic Research, 2022)
Incretins including glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1), which are secreted from the small intestine after oral food ingestion, are currently well-known to stimulate insulin secretion from pancreatic β-cells and used for the treatment of type 2 diabetes mellitus. We have previously reported that prostaglandin F2α (PGF2α) stimulates the synthesis of interleukin-6 (IL-6) and osteoprotegerin in osteoblast-like MC3T3-E1 cells, and that IL-6 and osteoprotegerin release are mediated through the p44/p42 mitogen-activated protein (MAP) kinase, p38 MAP kinase or stress-activated protein kinase/c-Jun N-terminal kinase (SAPK/JNK) pathways. In the present study, we investigated the effects of incretins including GLP-1 and GIP, on the PGF2α-induced synthesis of IL-6 and osteoprotegerin and examined the detailed mechanism in osteoblast-like MC3T3-E1 cells. We found that GIP and GLP-1 significantly stimulated the PGF2α-induced synthesis of IL-6 in osteoblast-like MC3T3-E1 cells. In addition, GIP and GLP-1 significantly enhanced the PGF2α-induced mRNA expression levels of IL-6. On the other hand, GIP and GLP-1 markedly stimulated the PGF2α-induced synthesis of osteoprotegerin. However, the phosphorylation of p44/p42 MAP kinase, p38 MAP kinase, or JNK induced by PGF2α was not affected by GIP or GLP-1. Therefore, these results strongly suggest that incretins enhance the PGF2α-induced synthesis of IL-6 and osteoprotegerin in osteoblast-like MC3T3-E1 cells. However, these syntheses are not mediated through p44/p42 MAP kinase, p38 MAP kinase, or JNK pathways.
Keywords: glucose-dependent insulinotropic peptide; glucagon-like peptide-1; prostaglandin F2α; interleukin-6; osteoprotegerin; osteoblast